Academic Stress and Role Conflict On Psychological Well-Being In Working Students - Widyawati, Putu Eka; I. G. A. A. Noviekayati; Niken Titi Pratitis (South Sulawesi Education Development, 2026)
This study aims to examine the relationship between academic stress and role conflict with psychological well-being among working students in Surabaya. A quantitative correlational design was employed using multiple regression analysis. The population consisted of undergraduate students who were simultaneously working while studying at several universities in Surabaya. A total of 162 participants were recruited using quota sampling based on inclusion criteria: active student status, currently employed (part-time or full-time), and aged between 18–30 years. Psychological well-being was operationalized based on Ryff’s six dimensions (self-acceptance, positive relations, autonomy, environmental mastery, purpose in life, and personal growth). Academic stress was defined as perceived academic pressure related to academic demands, while role conflict referred to incompatibility between work and study roles (work interfering with study and study interfering with work). Data were collected through validated Likert-scale instruments and analyzed using SPSS after fulfilling classical assumption tests. The results showed that academic stress did not significantly predict psychological well-being. However, role conflict had a significant negative relationship with psychological well-being (p < 0.05), with an effective contribution of 2.6%. These findings indicate that role incompatibility plays a more critical role than academic pressure in explaining well-being among working students. The study highlights the importance of role management strategies and institutional support systems in maintaining psychological well-being among students with dual responsibilities.